SWISS BALL EXERCISE DAN KOREKSI POSTUR TDAK TERBUKTI LEBIH BAIK DALAM MEMPERKECIL DERAJAT SKOLIOSIS IDIOPHATIK DARIPADA KLAPP EXERCISE DAN KOREKSI POSTUR PADA ANAK USIA 11 – 13 TAHUN - Sari, Suriani; Tirtayasa, Ketut; -, Sugijanto (Sport and Fitness Journal, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Scoliosis is abnormalities in skeletal form of the curvature of the spine , where the spine bending occurs towards the left or right side or abnormalities spine in the form of C or S. Common Signs of scoliosis include different shoulder bone , protruding shoulder blades , spine curvature real , pelvic tilt, the difference between arm and body space. Degree of scoliosis can be known with adam forwar d Bending and inclinometer test. The purpose of this study was to determine effectiv ity of swiss ball exercise training and posture correction and training effectiveness Klapp and posture correction exercise in reducing the scoliosis degree in children aged 11-13 years . This type of research was experimental design with pre and post contol group . In this study , 15 respondents were given swiss ball exercise training and 15 respondents were given Klapp excercise training . Each posture correction treatment was given every activity . Exercises performed with 45-minute frequency of 3 times a week for 12 weeks of data in the form of pre test and post test . Obtained by decreasing the degree of scoliosis . The results of this study are in the treatment group swiss ball exercise training the degree of scoliosis occurs with mean difference value of p < 0.05 and showed a significant difference . While in the commission of exercise training occurs Klapp mean difference degrees of scoliosis with a value of p < 0.05 and showed a significant difference . The conclusion of this study is the combination of swiss ball exercises and posture correction equally effective in reducing the degree of scoliosis with Klapp combination of exercise and posture correction in children aged 11-13 years . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Swiss Ball Exercise , Klapp Exercise, The Degree of Scoliosis